PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DI KELAS IV SD NEGERI 157618 HUTAGURGUR I - Yolanda Silaban, Veronika; Arifin, Mohd.; Dewi, Nova Christina (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The Problem In This Research Is The Low Mathematics Learning Outcomes Of Students In The Material Of Simple Room Building In Grade IV SD Negeri 157618 Hutagurgur I, To Overcome This Problem In This Study The Application Of The Quantum Teaching Learning Model., This Research Is A Classroom Action Research. From The Results Of The Initial Test It Was Found That The Lowest Score Was 21 And The Highest Score Was 86. Studied) As Many As 13 People (59.09%). And The Mean Value Of The Initial Test Was 63.59. After Giving Action In Cycle I Through The Stages Of Implementing The Quantum Teaching Learning Model, At The End Of The Lesson, The Students Were Given A Test Of Learning Outcomes, So The Class Average Value Was 77.27. In The First Learning Outcome Test, It Can Be Seen That There Were 19 Students Who Completed Learning (86.36%) And 3 Students Who Did Not Complete The Study (13.64%).Based On The Results Of The Above Research, It Can Be Concluded That The Application Of The Quantum Teaching Learning Model Can Improve Student Learning Outcomes In Simple Building Materials In Class IV SD Negeri 157618 Hutagurgur I.